Molecular assessment of maize inbred lines (Zea mays L.) Using microsatellite markers - Maniruzzaman, -; Azam, MG; Islam, S; Hossain, MG; Rohman, MM (Bangladesh Journal of Agricultural Research, 2018)
Genetic diversity analysis and germplasm characterization are essential steps in plant breeding and molecular markers are proved tool to accomplish. The present study was undertaken at the Molecular Breeding Lab of Plant Breeding Division, Bangladesh Agricultural Research Institute (BARI) to determine the genetic relatedness and molecular characterization of 15 maize inbred lines of BARI. In present study, genetic diversity analysis was performed by using 10 SSR primers to evaluate the polymorphisms, among them six primers showed distinct polymorphism between the maize inbred lines. The maize genotypes E81, E144, E08, E167, E102, E142 and E121 were found more diverged (0.9003) compared to other inbred lines. On the other hand, the lowest genetic distance values (0.1501) were found between the genotype E140 and genotype E80 followed by genotype E126 and genotype E140; genotype E140 and genotype E65; genotype E65 and genotype E80 values were identical (0.4502). The genotypes viz. E81, E144, E08, E167, E102, E142 and E121 were found far away from centroid of the cluster and rest of the genotypes were placed around the centroid. The Principal Coordinate Analysis (PCO) helped to visualize four major clusters and showed that seven maize inbred lines (E81, E58, E08, E167, E102, E142 and E121) were far away from the other genotypes. In conclusion, SSR markers enabled discrimination among accessions and provided valuable information for future use in improvement of these genomic resources. Bangladesh J. Agril. Res. 43(4): 533-542, December 2018